Development of new baseball pitching machine with four-roller throwing mechanism - Sakai, S.; Shi, J. X. (Proceedings, 2020)
At present, there are only a few developed pitching machines that can throw a ball with gyro spin. In this study, we aimed to develop a new baseball pitching machine using four rollers, where the rotational speed of each of the four rollers and the crossing angle of the opposite gyro rollers can be controlled optionally to generate an objective gyro spin more efficiently. We also elucidate the throwing mechanism of the developed baseball pitching machine and confirm its performance by finite element analysis. The newly developed pitching machine can throw a baseball with a wide range of speeds from 22.2 m/s (80 km/h) to 44.4 m/s (160 km/h) with all pitch types (fastball, curveball, gyroball, etc.), and the spin axis can be controlled in any designated direction. Moreover, this machine is capable of throwing a baseball with higher accuracy compared to commercially available pitching machines.